Prediction of Single-Stage Limit Language and Adult Language via Yusof-Goode Approach - Wen, Li Lim; Yuhani, Yusof; Norhayati, Rosli (2014)
Yusof-Goode (Y-G) rule, a new symbolization of representing rule in splicing system under framework of formal language theory to model the recombinant behaviors of DNA molecules, was introduced by Yusof in 2012. A language that contains the strings resulting from a splicing system is called splicing language. Limit language is a subset of splicing language where it is restricted to the molecules that will be present in the system after the reaction has run to completion. Adult language is a subset of limit language where it does not participate in further splicing. In this paper, the new concept of single stage splicing languages is introduced and some theorems have been formulated to stipulate the final state product of single stage limit languages of Yusof-Goode splicing system based on the characteristic of one initial string andone rule.